Novas considerações sobre o papel da lâmina crivosa no glaucoma: revisão bibliográfica - Andrade, Julia Corradi De Faria [UNIFESP] (2019)
Purpose: To identify the lamina cribrosa (LC) changes related to the development and progression of glaucoma from the available studies in the current literature. Provide future directions based on a critical data analysis, focusing on its clinical relevance and day-to-day applicability. Methods: A literature review on the topics LC and glaucoma using Latin American and Caribbean Literature in Health Sciences (LILACS) databases - Latin American Center and Caribbean Region of Health Sciences Information Regional Medicine Library (BIREME), PUBMED, and Scientific Eletronic Library Online (Scielo). As inclusion criteria, were selected articles (full text) in Portuguese, English, Spanish or French languages, which have been published in the last twenty years (January 1998 to January 2018). Articles considered of relevance for the understanding of some topics were also included, even if published prior to the pre-defined time interval. The authors used the following descriptors: “lamina cribrosa”, “cribiform plate”, “glaucoma” and “optical coherence tomography (OCT)”, “Enhanced Depth Imaging OCT (EDI-OCT)” and “Swept Source OCT (SS-OCT)”. Results: Several morphological alterations of the lamina cribrosa have been described in vivo after the evolution of OCT devices, more pronounced after the advent of Spectral Domain (SD-OCT), EDI-OCT and SS-OCT. After optimizing the visualization of the deeper structures, the studies investigated laminar anatomical changes in glaucomatous eyes and the most relevant findings were the reduction of laminar thickness, the presence of localized defects and the posterior LC displacement (based on the anterior laminar depth, ALD). The comparison of these findings with normal eyes showed that the analysis of the laminar thickness has a good diagnostic performance, comparable with conventional OCT parameters. Currently, laminar changes have been investigated as predictive factors for glaucoma progression and some authors have shown that laminar thickness appears to vary according to the type of glaucoma and the severity of the disease, and would possibly be an independent risk factor for glaucoma progression. In addition, the authors observed that the presence of posterior LC displacement (deeper ALD) is more frequent in glaucomatous eyes, even in the early stages of the disease. In addition, eyes with deeper ALD had a faster structural and functional progression, and the magnitude of posterior displacement was an independent risk factor for disease progression. Finally, it should be noted that it is not always possible to visualize the posterior laminar face, which makes it difficult to measure the thickness of the lamina in certain cases. Conclusions: Morphological alterations documented using new OCT technologies are promising as possible additional tools for glaucoma diagnosis and follow-up, and new laminar parameters have emerged as predictors of disease progression. Despite the advance of technology, proper evaluation of the lamina cribrosa is not yet possible in all eyes. For future guidelines, we believe that a more detailed knowledge of the biomechanical behavior of the LC could not only provide new susceptibility parameters, but also offer new therapeutic options for the management of glaucoma, focused on modifying the laminar biomechanics.